2020
DOI: 10.4081/jphr.2020.1787
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Cardiac Self-Efficacy among Patients Diagnosed with Coronary Artery Disease in Tertiary Hospitals in Nepal

Abstract: Background: Cardiac self-efficacy determines how people feel, think, motivate themselves and behave with regards to improving their cardiac health subsequently preventing complications of coronary artery disease (CAD). Given almost one-third of global death is contributed by CAD with 10% of disability adjusted life years lost in low- and middle-income countries (including Nepal), it is important to identify factors that can promote cardiac self-efficacy. There are no studies in Nepal focusing on predictors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 20 publications
0
31
1
Order By: Relevance
“…( 28 ) One study has shown that a one-unit increase in health-related behaviors and heart-related knowledge can raise self-efficacy in managing the prevention of cardiovascular diseases by 0.432 and 0.475 units, respectively. ( 29 )…”
Section: Discussionmentioning
confidence: 99%
“…( 28 ) One study has shown that a one-unit increase in health-related behaviors and heart-related knowledge can raise self-efficacy in managing the prevention of cardiovascular diseases by 0.432 and 0.475 units, respectively. ( 29 )…”
Section: Discussionmentioning
confidence: 99%
“…This inconsistency of self-efficacy level could be attributed to many factors that can influence cardiac self-efficacy among patients, such as age, health behaviors, and knowledge of the disease, which are the strongest predictors of cardiac self-efficacy. 33 Other factors that could influence the variations in self-efficacy levels in the literature may be attributed to different cardiac populations that were recruited in previous studies, and different methodologies and research outcomes that were used in the studies. This also relates to the absence of cardiac rehabilitation programs in Jordan (and the Middle East in general).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the findings of the study were inconsistent with those of Barham et al, 32 who found that patients with coronary heart disease had a low self-efficacy level in a Palestinian population after hospitalization. This inconsistency of self-efficacy level could be attributed to many factors that can influence cardiac self-efficacy among patients, such as age, health behaviors, and knowledge of the disease, which are the strongest predictors of cardiac self-efficacy 33 . Other factors that could influence the variations in self-efficacy levels in the literature may be attributed to different cardiac populations that were recruited in previous studies, and different methodologies and research outcomes that were used in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the relationship between self-efficacy and quality of life in patients with coronary heart disease (RoshanGhias et al, 2018;Sarkar et al, 2007;Shrestha et al, 2020). Selfefficacy plays a crucial role in enhancing patients' quality of life (Brink et al, 2012;Shrestha et al, 2020).…”
Section: Introductionmentioning
confidence: 99%